Nutritive Value of Mulberry (Morus Alba) Hay as a Feed Supplement for Sheep - Ali, Arsyadi (2006)
A study comprising of three experiments was conducted on the utilization of mulberry (Morus alba) hay as feed supplement in sheep. The first experiment determined the duration of the sun-drying of mulberry foliage until it reached 10% moisture content and the nutritive values of the hay five (W5) and seven weeks (W7) old forage. The second experiment elucidated the characteristics of the hay with respect to in situ degradation of dry matter (DM) and crude protein (CP). The third experiment determined the effect of supplementation of mulberry hay on the total digestibility of the ration based on oil palm frond (OPF) pellet. The drying time of W7 mulberry foliage was significantly (P<0.05) longer than W5. The drying time of stem was significantly (P<0.05) longer than leaf fraction at both ages of maturity (W5 and W7). The DM and neutral detergent fiber (NDF) content of mulberry was not significantly (P>0.05) different with advancing plant maturity, but increased significantly (P<0.05) with the drying process. The CP content of mulberry decreased with the plant maturity (W5 to W7) and the drying process. The ash content was affected by the advancing plant maturity, drying and plant fraction. The acid detergent fiber (ADF) and acid detergent lignin (ADL) content increased with plant maturity (W5 to W7) and was not affected by drying. The DM degradation of mulberry harvested at 5 weeks of age and oven-dried (MHO5) and mulberry harvested at 5 weeks of age and sun-dried (MHS5) was significantly (P<0.05) higher than mulberry harvested at 7 weeks of age and oven dried (MHO7) and mulberry harvested at 7 weeks of age and sun-dried (MHS7) at 12, 24, 36 and 48 h of rumen incubation. Meanwhile, the CP degradation of MHO5, MHS5, MHO7 and MHS7 was not significantly (P>0.05) different at 0, 6, 12, 24, 36 and 48 h of incubation. The degradability of water insoluble (b), potential degradability (PD) and effective degradability (ED) of DM of MHO5 and MHS5 were higher than MHO7 and MHS7. Meanwhile, the PD and ED of CP were significantly (P<0.05) decreased with advancing plant maturity. Supplementation of mulberry hay to OPF pellet based diet from 20 to 60% increased the DM, organic matter (OM), CP, NDF digestibility, N intake and absorption and NH3-N concentration. Increasing level of mulberry hay supplementation did not influence total dry matter intake (DMI), N retention and total volatile fatty acid (VFA). Mulberry hay of 5 weeks compared to 7 weeks old forage contained higher CP, lower cell wall and lignin content and higher DM degradability, ED and PD values. Supplementation of mulberry hay as a CP source significantly (P<0.05) improved the utilization of OPF pellet as base diet in sheep. However, higher level of mulberry hay supplementation is not recommended because it did not increase the total DMI and N retention.